Differential accumulation and distribution of natural gas and its main controlling factors in the Sinian Dengying Fm, Sichuan Basin - Shugen Liu; Wei Sun; Yihua Zhao; Guozhi Wang; Linke Song; Bin Deng; Feng Liang; Jinmin Song (Natural Gas Industry B, 2015)
In order to disclose the genetic relationship between the hydrocarbon reservoirs and the transformation mechanism between ancient and modern gas reservoirs in the Sinian Dengying Fm in the Sichuan Basin, by using the drilling data, and geologic, geophysical and geochemical methods together, the differential accumulation and distribution of natural gas and its main controlling factors in this study area were identified following the idea of corroborating macroscopic, mesoscopic and microscopic results each other. The results demonstrate as follows. (1) The crude oil in the paleo-oil reservoirs of the Dengying Fm cracked into gas to form the early overpressure paleo-gas reservoirs 100 Ma. From 100 Ma to 20 Ma, the constant uplifting of the Sichuan Basin coupled with the shift of structural highs and the initial occurrence of Weiyuan anticline caused the adjustment of the early overpressure paleo-gas reservoirs into the late overpressure paleo-gas reservoirs. (2) With the increase of uplifting magnitude since 20 Ma, the formations overlying the Dengying Fm in Weiyuan structure experienced rapid erosion, resulting in decline of the caprock sealing ability and damage to the preservation conditions. Therefore, the natural gas in the Dengying Fm started to leak and dissipate from the eroded window of the Lower Triassic Jialingjiang Fm located on the top of the Weiyuan anticline, which is the beginning of the differential accumulation and dissipation of the natural gas in the Dengying Fm across the Sichuan Basin. During the process of the differential accumulation and dissipation, the gas below the spill point of the structural gas traps in Ziyang, Jinshi and Longnüsi–Moxi–Anpingdian–Gaoshiti areas migrated to the Weiyuan anticline along the unconformity of the Dengying Fm, and dissipated through the eroded window of the Jialingjiang Fm on the top of the Weiyuan anticline, resulting in a transformation of abnormal high pressure of gas reservoir to normal pressure in the Dengying Fm. The differential accumulation and dissipation mode in the Dengying Fm in the Sichuan Basin has both similarities with and differences from the classic hydrocarbon differential entrapment theory, and will give great inspiration to and guide the further gas exploration in the Sichuan Basin.